Answer:
7 feet
Step-by-step explanation:
(3h + 4)² = 24² + h²
9h² + 24h + 16 = 576 + h²
8h² + 24h - 560 = 0
h² + 3h - 70 = 0
(h + 10)(h - 7) = 0
h = 7' (h cannot be -10)
Answer:
4
Step-by-step explanation:
y = -x + 4
if y = 0, then
0 = -x + 4
x = 4
Answer:
4-6x
Step-by-step explanation
Answer:
A
Step-by-step explanation:
A. 3 imaginary; 2 real
B. 4 imaginary; 1 real
C. 0 imaginary; 5 real
D. 2 imaginary; 3 real
Answer:
B. 4 imaginary; 1 real
Step-by-step explanation:
Given the polynomial:
x^5 + 7*x^4 + 2*x^3 + 14*x^2 + x + 7
it can be reordered as follows
(x^5 + 2*x^3 + x ) + (7*x^4 + 14*x^2 + 7)
Taking greatest common factor at each parenthesis
x*(x^4 + 2*x^2 + 1) + 7*(x^4 + 2*x^2 + 1)
Taking again the greatest common factor
(x + 7)*(x^4 + 2*x^2 + 1)
Replacing x^2 = y in the second parenthesis
(x + 7)*(y^2 + 2*y + 1)
(x + 7)*(y + 1)^2
Coming back to x variable
(x + 7)*(x^2 + 1)^2
There are two options to find the roots
(x + 7) = 0
or
(x^2 + 1)^2 = 0 which is the same that (x^2 + 1) = 0
In the former case, x = -7 is the real root. In the latter, (x^2 + 1) = 0 has no real solution. Therefore, there is only 1 real root in the polynomial.
□44
□19
□17
□11
Answer:
11
Step-by-step explanation:
3 (4 - n) + 8
When n = 3:
3 (4 - 3) + 8
3 (1) + 8
3 + 8
11
Answer:
11
Step-by-step explanation: